2020
DOI: 10.7150/jca.36203
|View full text |Cite
|
Sign up to set email alerts
|

Critical role and its underlying molecular events of the plasminogen receptor, S100A10 in malignant tumor and non-tumor diseases

Abstract: S100A10 is a small molecular weight protein expressed in the cytoplasm of many cells and one of the members of the S100 protein family that binds calcium and forms the largest subgroup of EF-hand proteins. The regulatory processes of S100A10 are complicated. S100A10 participates in the regulation of a variety of tumor and non-tumor diseases through cascade reactions with multitudinous signaling molecules. In malignant tumors, such as acute promyelocytic leukemia (APL) and lung cancer, S100A10 is likely involve… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
34
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(35 citation statements)
references
References 97 publications
(112 reference statements)
0
34
0
Order By: Relevance
“…Previous studies reported the association between the mutations of RAS oncogene, especially KRAS, and high frequency of TB [8,30]. S100A10 is also considered to contribute to ECM degradation as well as cancer development, invasion, and metastasis via cell surface plasmin generation and RAS cooperation, including KRAS [11,12,17]. A few studies reported the relationship between S100A10 and Wnt pathway [31], whereas a recent study suggested that S100A10 is a key regulator of the plasminogen activation system during TGF-β-induced EMT [20].…”
Section: Discussionmentioning
confidence: 99%
See 2 more Smart Citations
“…Previous studies reported the association between the mutations of RAS oncogene, especially KRAS, and high frequency of TB [8,30]. S100A10 is also considered to contribute to ECM degradation as well as cancer development, invasion, and metastasis via cell surface plasmin generation and RAS cooperation, including KRAS [11,12,17]. A few studies reported the relationship between S100A10 and Wnt pathway [31], whereas a recent study suggested that S100A10 is a key regulator of the plasminogen activation system during TGF-β-induced EMT [20].…”
Section: Discussionmentioning
confidence: 99%
“…However, the reason why the protein complex is highly expressed in TB/PDC remains unclear, indicating the collapse of the cell polarity. In poorly differentiated cancer cells, the functions of S100A10-ANX A2 heterocomplex are out of balance and that another function, such as promotion of cell migration/invasion [11,12,23,35,38,40], becomes dominant. Hence, future studies will be necessary to con rm the aforementioned research question.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, changes in the expressions and/or functions of the S100 proteins are key steps in cancer development or progression [ 10 ]. S100A10, a member of the S100 protein family, is also expressed in various cells, including cancer cells [ 11 , 12 ]. S100A10 forms a heterocomplex with cytoplasmic annexin A2 (ANX A2), then translocates to the cell membrane from the cytoplasm, and plays various roles in cell dynamics [ 11 , 12 ].…”
Section: Introductionmentioning
confidence: 99%
“…S100A10, a member of the S100 protein family, is also expressed in various cells, including cancer cells [ 11 , 12 ]. S100A10 forms a heterocomplex with cytoplasmic annexin A2 (ANX A2), then translocates to the cell membrane from the cytoplasm, and plays various roles in cell dynamics [ 11 , 12 ]. It is well known that the S100A10-ANX A2 heterocomplex functions as a plasminogen receptor and promotes cell migration/invasion [ 11 – 17 ].…”
Section: Introductionmentioning
confidence: 99%